Assessing stakeholder inclusion within high pathogenicity avian influenza risk governance strategies in the United Kingdom and United States - Lyons, Kimberly; Kapczynski, Darrell R.; Lycett, Samantha J.; Digard, Paul; Boden, Lisa (Frontiers in Veterinary Science, 2025)
Since 2020, outbreaks of high pathogenicity avian influenza (HPAI) have led to a global rise in deaths of both wild birds and poultry, as well as an increase in reported cases of HPAI detected in mammals. These outbreaks have had negative impacts on poultry producers, trade, and wild bird populations. Risk governance frameworks for emerging infectious diseases such as HPAI encourage outbreak policies to be grounded in a variety of stakeholder perspectives and for there to be effective, transparent communication between all those involved. However, the COVID-19 pandemic exemplified how collaboration is not always easy to implement, leading to potentially sub-optimal outbreak response processes. To our best knowledge, there is limited to no current research assessing the stakeholder landscape and outbreak decision-making and response processes in the United Kingdom (UK) and United States of America (USA) for the recent HPAI outbreak. In this study, 20 key stakeholders involved in outbreak decision-making and response in the United Kingdom and United States were asked to provide their insights into the structure of stakeholder landscape, communication pathways, and challenges in decision-making and response implementation for their respective countries. Semi-structured interviews were conducted with participants from the United Kingdom and United States; participants included policy advisors, veterinarians, researchers, and poultry industry representatives all involved in HPAI outbreak processes in their country. From these interviews, stakeholder maps for all those involved in HPAI decision-making and response were created for the UK and USA. This study concluded that smallholders and backyard poultry owners need to be better represented in policy-industry communication pathways and that improved information sharing at the policy-science and policy-industry interfaces is essential to ensure an efficient outbreak response.